Production and Optimization of Bio-Based Silica Nanoparticle from Teff Straw (Eragrostis tef) Using RSM-Based Modeling, Characterization Aspects, and Adsorption Efficacy of Methyl Orange Dye - Temesgen Abeto Amibo; Surafel Mustefa Beyan; Tsegaye Markos Damite (Journal of Chemistry)
The brown teff straw was utilized in this study to produce silica using the sol-gel technique. After pretreatment, the raw material of brown teff straw was characterized. The data were analyzed using the central composite design and response surface technique, and four independent parameters, namely, temperature, NaOH concentration, rotational speed, and extraction time, were evaluated for process optimization. Before extracting silica with an alkaline solution, the silica content in the ash was determined using an AAS spectrometer. The silica content of teff straw ash is around 92.89%. The ash was treated with NaOH solution in the concentrations range of 1 M to 3 M (0.5 M interval). The extraction time varied at intervals of 55, 70, 85, 100, and 115 minutes. Temperatures were changed using magnetic stirrer equipment in the range of 80°C to 100°C (5°C interval). At 350 rpm, 400 rpm, 450 rpm, 500 rpm, and 550 rpm, the rotating speed was adjusted. The best extraction conditions for amorphous silica were 1.50 M NaOH, 109.99 min, 94.98°C, and a rotating speed of 499.57 rpm, with a maximum yield of 85.85%. XRD and FTIR analyses were used to assess the physicochemical characteristics of the extracted silica. The aqueous solutions of methyl orange were used to test the adsorption efficiency of silica. The percent of removal efficiency for methyl orange was 90.48%.